Positive mental health and sense of coherence among emergency medical service professionals - Mantas-Jiménez, Susana; Reig-García, Glòria; Roqueta-Vall-Llosera, Marta; Camara-Liebana, David; Masià-Plana, Afra; Lluch-Canut, Maria Teresa; Juvinya-Canal, Dolors (Frontiers in Public Health, 2024)
Background Positive mental health (PMH) is a construct used to define and evaluate health from a positive perspective. Healthcare professionals in the emergency ambulance service are more likely to experience mental health disorders than the overall population. The demographic and occupational variables and Sense of Coherence (SOC) can act as predictors of PMH and can serve as protective elements against stress and demanding situations in the work environment. Objective This study aimed to evaluate PMH and its relationship with demographic and occupational variables and determine if SOC is a predictive variable for PMH in health professionals working in the emergency ambulance service. Methods A descriptive, cross-sectional, and correlational study was conducted with a sample of 406 healthcare professionals from the emergency ambulance service in eight health regions of Catalonia, Spain. The following variables were analyzed: Age, biological sex, household members, dependents family members, professional category, type of contract, job satisfaction and sense of collaboration with other institutions. The following assessment instruments were used: Positive Mental Health Questionnaire and Sense of Coherence scale. Results High scores were obtained in Positive Mental Health (PMH). Study participants who reported feeling completely satisfied in their work also showed a significant relationship with all PMH factors: greater satisfaction with their personal life, in their helpful prosocial attitude toward others, in their capability to deal effectively with stress and navigate conflict scenarios, in their ability to solve problems and self-realization, greater empathy and ability to understand the feelings of others, greater ability to establish interpersonal relationships. Comprehensibility, as a dimension of SOC, was identified as a predictor for some factors of PMH: a greater personal satisfaction, self-control, autonomy, interpersonal skills and total PMHQ. More than 43% of positive mental health in health professionals is explained by higher Meaningfulness and Comprehensibility values of the SOC, the absence of dependent family members and having a non-graduate background. Conclusion Healthcare workers in the emergency ambulance service had high PMH. Meaningfulness (ME) and Comprehensibility (C), dimensions of SOC, were identified as model predictors of greater PMH, showing higher scores in most of PMH factors. To enhance SOC as a mental health promotion measure, resilience programs should be implemented to help professionals develop skills to face and overcome adverse situations. Educating in stress management thought networks are key elements to strengthen SOC. Managers in emergency medical services play a key role in transforming healthcare work environments to promote positive outcomes in the mental health of their healthcare workers.